Analisis Putusan Mahkamah Konstitusi Nomor 93/PUU-XX/2022 Terhadap Pengampuan Bagi Penyandang Disabilitas Mental - Azzahra, Haliza; Firdaus, Sunny Ummul; Achmad, Achmad (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2025)
This legal research aims to examine and analyze the Constitutional Court Decision Number 93/PUU-XX/2022 related to the judicial review of Article 433 of the Civil Code about Guardianship. The research method used is a normative or doctrinal legal research method with a case approach. The legal material collection technique used is library research. This research uses qualitative analysis techniques, which are rooted in the major premise and then propose the minor premise. Based on this research, the results obtained were that judges used historical, grammatical and systematic interpretation methods in their considerations. The judge partially granted the request and declared that Article 433 of the Civil Code was conditionally unconstitutional. In the aspect of legal protection for people with mental disabilities, the indicator used in this research is Article 9 of Law Number 8 of 2016 concerning Persons with Disabilities. Of the nine indicators in this article, it was found that the continued existence of the guardianship system means that the rights stated in Article 9 of the Law on Persons with Disabilities cannot all be fulfilled, so that legal protection for people with mental disabilities is not yet optimal.